2009
DOI: 10.1007/s11409-009-9052-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in relative metacomprehension accuracy: variation within and across task manipulations

Abstract: In recent decades, increasing numbers of studies have focused on metacomprehension accuracy, or readers' ability to distinguish between texts comprehended more vs. less well. Following early findings that suggested readers are fairly poor at doing so, a number of studies have identified specific tasks to supplement a single reading of text that have resulted in greater metacomprehension accuracy. One assumption underlying these studies is that, in the absence of such tasks, metacomprehension accuracy is unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…This outcome supports the theoretical distinction between the two mechanisms: Interventions like selfexplaining enable the generation of situation-model cues, whereas rereading enhances the attention to the cues (Griffin et al 2008, Experiment 2). It should be noted, however, that some studies did not find a benefit of rereading over reading once (Chiang et al 2010;Margolin and Snyder 2018), and, in some studies, learners exhibited low relative metacomprehension accuracy despite rereading (Bugg and McDaniel 2012;Pao 2014;, Experiment 1).…”
Section: Cue-attention Interventionmentioning
confidence: 88%
“…This outcome supports the theoretical distinction between the two mechanisms: Interventions like selfexplaining enable the generation of situation-model cues, whereas rereading enhances the attention to the cues (Griffin et al 2008, Experiment 2). It should be noted, however, that some studies did not find a benefit of rereading over reading once (Chiang et al 2010;Margolin and Snyder 2018), and, in some studies, learners exhibited low relative metacomprehension accuracy despite rereading (Bugg and McDaniel 2012;Pao 2014;, Experiment 1).…”
Section: Cue-attention Interventionmentioning
confidence: 88%
“…For instance, previous studies found that individuals with high working memory capacity (S. Chen, 2010;Chiang, 2007;Chiang, Therriault, & Franks, 2010;Ni, 2019), high reading ability (Ozuru, Kurby, & McNamara, 2012), and high comprehension ability (Griffin et al, 2008) made more accurate comprehension judgments, and these individuals also performed better on criterion tests.…”
Section: Poor-comprehensionmentioning
confidence: 99%
“…Εξαιτίας της δυσκολίας που αντιμετωπίζουν τα παιδιά σχολικής ηλικίας αλλά και ενήλικες στην ανίχνευση κυρίως εσωτερικών αντιφάσεων στο περιεχόμενο κειμένων, το ερευνητικό ενδιαφέρον των μελετητών επικεντρώθηκε στον εντοπισμό των παραγόντων που εμπλέκονται στη διαδικασία της παρακολούθησης της κατανόησης και συμβάλλουν στην παρουσία ενός υψηλού επιπέδου ακρίβειας στην παρακολούθηση (π.χ., Anderson et al, 2008. Chiang et al, 2010.…”
Section: κατανοηση κειμενουunclassified
“…(αναλυτική περιγραφή των παραγόντων που επηρεάζουν την κατανόηση κειμένου παρουσιάζονται αναλυτικά στο Κεφάλαιο 1). Στόχος αυτών των ερευνών είναι ο εντοπισμός εκείνων των παραγόντων που συμβάλλουν στην παρουσία ενός υψηλού επιπέδου ακρίβειας στην παρακολούθηση της κατανόησης (π.χ.,Anderson et al, 2008. Chiang et al, 2010.…”
unclassified